Global Research Dynamics: A Bibliometric Exploration of Child Education in Artisanal Mining - Vieronica Varbi Sununianti; Rudy Kurniawan; Nurilla Elysa Putri (Journal of Innovation in Educational and Cultural Research, 2025)
This study investigates the trends in child education and artisanal mining research over the past two decades, aiming to provide a quantitative analysis of the network structure within these studies. The research utilizes a bibliometric method to analyze scientific publications from the Scopus database, with results visualized using VOSviewer. A total of 208 documents from multiple countries were examined. The findings reveal that Galvin Hilson is this field's most prolific and influential author. The United Kingdom leads in terms of publication volume and citations, followed by Canada and China. The Journal of Extractive Industries and Society is the most prominent journal by volume, while the Journal of Science of The Total Environment stands out for having the highest number of citations (930). The most cited article is “Contamination Features and Health Risk of Soil Heavy Metals in China” by Chen et al. The dominant topic explored is artisanal and small-scale gold mining in Sub-Saharan Africa. While child labor remains a primary focus, the relationship between education, poverty, and socioeconomic improvements is underexplored. This study highlights the need for further research on how socioeconomic changes influence children’s education and the broader context of artisanal mining across developing nations.